Haptic and audio interaction design : third international workshop, HAID 2008, Jyväskylä, Finland, September 15-16 2008 ; proceedings - Pirhonen, Antti (Springer, 2017)
This book constitutes the refereed proceedings of the Third International Workshop on Haptic and Audio Interaction Design, HAID 2008 held in Jyväskylä, Finland, in September 2008.